The Effect Of Crossword Puzzle Game On Students' Vocabulary Mastery At Grade Eight Of SMP GKPS 3 Pematang Siantar - Citra Julivera Nainggolan; Christian Neni Purba; Melda Veby Ristella Munthe (CV Putra Publisher, 2024)
The aim of this study is to find out whether crossword puzzle game is an effective media to improve students’ vocabulary mastery of descriptive text, and comparing with the students who were taught by using the conventional media. This study is a quantitative research using quasi-experimental as the method of collecting data. In this study, the data were taken from the pre-test and post-test. The Excel program was used to analyze the validity. The result shows that the mean of pre-test from the experimental group was 55,33, and the control group was 42,33. Then the mean of post-test from the experimental group was 82,5, and the score of the control group was 63,16 Based on the t-test calculation of post-test from both classes shows that the result of the t-value (3,666) was higher than the t-table (2.001). Since the t-test was higher than the t-table, it could be stated that there was a significant difference between the students’ achievement who were taught by using crossword puzzle game and those who were taught by using conventional learning media in improving vocabulary of descriptive text. The students who were taught by using crossword puzzle game have higher achievement. In other words, crossword puzzle game is effective to improve students’ vocabulary mastery. Based on this result, it is recommended that teachers use crossword puzzle in English classes because this game is very helpful for students in improving their vocabulary mastery.